Data from: Phenotypic plasticity facilitates initial colonization of a novel environment - Wang, Sheng Pei; Althoff, David M. (Dryad, 2019)
Phenotypic plasticity can allow organisms to respond to environmental
changes by producing better matching phenotypes without any genetic
change. Because of this, plasticity is predicted to be a major mechanism
by which a population can survive the initial stage of colonizing a novel
environment. We tested this prediction by challenging wild Drosophila
melanogaster with increasingly extreme larval environments and then
examining expression of alcohol dehydrogenase (ADH) and its relationship
to larval survival in the first generation of encountering a novel
environment. We found that most families responded in the adaptive
direction of increased ADH activity in higher alcohol environments and
families with higher plasticity were also more likely to survive in the
highest alcohol environment. Thus, plasticity of ADH activity was
positively selected in the most extreme environment and was a key trait
influencing fitness. Furthermore, there was significant heritability of
ADH plasticity which can allow plasticity to evolve in subsequent
generations after initial colonization. The adaptive value of plasticity,
however, was only evident in the most extreme environment and had little
impact on fitness in less extreme environments. The results provide one of
the first direct test of the adaptive role of phenotypic plasticity in
colonizing a novel environment.
Larval weight, ADH activity and family structureThe "egg" tab
contains the number of eggs collected from each female on different days.
The "weight" tab contains the information on the number and
weight of third instar larvae that's collected from each rearing
vial. The "dataADHactivity" contains the data on all ADH
activity measures.PPcolonization.xlsxR code for AnalysisR code for the
analyses.Analysis.R
Keywords: 2016; 2015